2015
DOI: 10.1371/journal.pone.0130876
|View full text |Cite
|
Sign up to set email alerts
|

Associations between Dietary Antioxidant Intake and Metabolic Syndrome

Abstract: BackgroundThe objective of this study was to evaluate the association between dietary antioxidant intake (carotenoid, vitamin C, E and selenium) intake and metabolic syndrome (MS).MethodThis cross-sectional study included 2069 subjects undergoing a regular health checkup. Biochemical test results and data on dietary intakes were collected for analysis. Adjustment for energy intake and multi-variable logistic regression were performed to determine adjusted odds ratios (ORs) and corresponding 95% confidence inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
67
2
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(74 citation statements)
references
References 33 publications
2
67
2
3
Order By: Relevance
“…However, findings regarding the association between antioxidant intake and the development of MS remain inconsistent. Wei et al [13] and Motamed et al [49] did not observe a significant association between the intake of vitamins A and E and the development of MS.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, findings regarding the association between antioxidant intake and the development of MS remain inconsistent. Wei et al [13] and Motamed et al [49] did not observe a significant association between the intake of vitamins A and E and the development of MS.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the adequate dietary ingestion of antioxidant micronutrients such as vitamins A, C and E, selenium and zinc minerals, may be a protective factor to prevent tissue damage arising from oxidative stress [12, 13]. Puchau et al showed that the dietary total antioxidant capacity may provide an estimation of the risk of development of MS components [48].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…1 Se status has therefore been related to different diseases, including metabolic syndrome (MS), 2 which is a pathological state defined as a cluster of risk factors, including central obesity, insulin resistance (IR), raised blood pressure and dyslipidemia, which may predispose an individual to cardiovascular diseases, diabetes and death. 6 However, a dual role for Se in IR and MS has been described. 5 Therefore, it could be supposed that dietary Se supplementation could have beneficial antioxidant effects in this pathology, increasing GPx activity.…”
Section: Introductionmentioning
confidence: 99%